2000
DOI: 10.1097/00002480-200011000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hemoglobin-Adenosine-Glutathione Based Blood Substitute: Evaluation of Its Effects on Human Blood Ex Vivo

Abstract: Chemically modified hemoglobin (Hb) solutions are under current investigation as potential red cell substitutes. Researchers at Texas Tech University have developed a novel free Hb based blood substitute product. This blood substitute is composed of purified bovine Hb cross-linked intramolecularly with o-adenosine-5'-triphosphate and intermolecularly with o-adenosine, and conjugated with reduced glutathione (GSH). In this study, we compared the effects of our novel blood substitute and unmodified (U) Hb, by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 74 publications
2
48
0
Order By: Relevance
“…According to corporate-produced literature, glutathione reduces the potential oxidative stress inherent in HBOCs (41) while adenosine provides anti-inflammatory activity and contributes to vasorelaxation (42). It is not clear that these would be achieved in circulation since no evidence is yet available to support the claims.…”
Section: Chemical Approaches That Deal With Hboc-induced Vasoconstricmentioning
confidence: 99%
“…According to corporate-produced literature, glutathione reduces the potential oxidative stress inherent in HBOCs (41) while adenosine provides anti-inflammatory activity and contributes to vasorelaxation (42). It is not clear that these would be achieved in circulation since no evidence is yet available to support the claims.…”
Section: Chemical Approaches That Deal With Hboc-induced Vasoconstricmentioning
confidence: 99%
“…Previous studies have demonstrated that lipid radicals are able to inhibit anti-apoptotic genes which allow a cell to enter into apoptosis. In these experiments, the presence of oxidative stress was evaluated by measuring lipid hyperperoxides (LOOH) and reduced glutathione (GSH) levels according to established methods [21,22].…”
Section: Studies Conducted On Gap-junctional Intracellular Communicatmentioning
confidence: 99%
“…Established methods were utilized to measure oxidative stress conditions to determine the concentration of GSH [21]. In a normal cell, GSH is unable to cross the nuclear membrane, but during oxidative stress the oxidized form of GSH, oxidized glutathione (GSSG), is able to cross this structure.…”
Section: Studies Conducted On Gap-junctional Intracellular Communicatmentioning
confidence: 99%
See 2 more Smart Citations